A Syntactical Spatio-Functional Analysis of Four Typical Historic Chinese Towns from a Heritage Tourism Perspective - Pan Liao; Rongrong Yu; Ning Gu; Sahar Soltani (Land, 2022)
This study presents a quantitative approach to exploring the spatio-functional characteristics of historic Chinese towns (HCTs) from a heritage tourism perspective. In recent years, HCTs have evolved from being resident-oriented to being more tourist-oriented, in part due to their heritage significance for attracting tourists. Spatio-functional qualities of a historic town are essential elements of the town’s urban morphology and of great concern for preservation. Previous studies that discussed this issue often used qualitative descriptions, and only limited studies have systematically explored the spatio-functional qualities of HCTs. Thus, there is presently a lack of understanding around this issue, especially based on rigorous quantitative approaches. This study examines the spatio-functional qualities of HCTs using space syntax, a commonly used method in urban studies that enables measurement of spatial characteristics through mathematical means. Four HCTs with heritage significance, Pingyao, Lijiang, Kulangsu, and Wuzhen, were selected as case studies. The study has examined the role of heritage tourism and the results show that tourist-focused functions tend to distribute and aggregate in the urban core of HCTs. By contrast, cultural relics are freely distributed and not expanded over time. Spatio-functional patterns of the four HCTs were theorised, and the paper concludes with suggestions regarding future land-use optimisation for the four HCTs concerning heritage tourism.